(3eLeY GdcfhRs - (3GdWGdbGfj, GdbRhjfj GdMGFQj, eMeO MSjf Hf Ydj, J (B1281 (3g`s ((3GdeUfas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd GdeMTj QMeg Gddg HSe Gddg GdQMef GdQMje , Cbhd GdcdGe ajgG jbY aj GdCehQ GdChd aj eJYdb GdHGA aeJYdbgG HMSH GdGMJeGdGJ GdYbdjI EeG GSe Ch aYd (B...s
(3BNQgG (B:s
.. (3dG jNai Ydjc Cf gPG UMjM aj GdYdhe GdYedjI hCeG aj GdYdhe GdfXQjI aGdebUhO efgG faSgG hdgPG GdfSH GdeMTj (B.. (3Gdbhd Ydi GdbjO aJCed (B. (3bO NJes
(3Ydi WQI GdeNWhW Cfg HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\255s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs